THE DIVERSITY AND ABUNDANCE OF SPIDERS (Arachnida) IN LIWA BOTANICAL GARDEN - Hajariyah Hajariyah; Nismah Nukmal; Gina Dania Pratami; M. Kanedi (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2020)
Spiders are organisms that can adapt to various environments throughout the earth's surface from arctic regions to desert areas. Many spiders occupy areas with low vegetation and shrubs. The Liwa Botanical Garden has dense vegetation which is an ideal habitat for spiders. This study aims to determine the diversity and abundance of spiders (arachnids) in open and closed areas in the Liwa Botanical Garden. The research was conducted in November - December 2019. Spiders were sampled using a survey method by making line transects at predetermined locations. Sampling using sweep nets and pit traps. The spiders found were identified in the Zoology Laboratory, Biology Department, Faculty of Mathematics and Natural Sciences, University of Lampung, and their relative abundance was calculated. The results showed that 249 individual spiders were grouped into 9 families and 21 species. The family with the highest number of individuals was Aranidae, while the least number of families was Phalangiidae.